James Buchanan - Baker, Jean H (New York Times Books, 2004)
A look at the presidency of James Buchanan, whose administration paved the way for the onslaught of the Civil War, details his failures as a president, including his lack of compromise and his weak leadership in a time of national crisis.
Ascension -- from Stony Batter to the Cabinet, 1791-1848 -- Wheatland to the White House, 1849-1856 -- The Buchanan Presidency -- Theory and Practice -- Appeasing the South: The Final Months of the Buchanan Presidency.
Includes bibliographical references (pages 159-161) and index.
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Buchanan, James -- 1791-1868.; residents -- United States -- Biography; United States -- Politics and government -- 1857-1861.